A Multi-institutional Comparison of Perioperative Outcomes of Robotic and Open Pancreaticoduodenectomy. Issue 4 (October 2016) - Zureikat, Amer H.; Postlewait, Lauren M.; Liu, Yuan; Gillespie, Theresa W.; Weber, Sharon M.; Abbott, Daniel E.; Ahmad, Syed A.; Maithel, Shishir K.; Hogg, Melissa E.; Zenati, Mazen; Cho, Clifford S.; Salem, Ahmed; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: Limited data exist comparing robotic and open approaches to pancreaticoduodenectomy (PD). We performed a multicenter comparison of perioperative outcomes of robotic PD (RPD) and open PD (OPD). Methods: Perioperative data for patients who underwent postlearning curve PD at 8 centers (8/2011–1/2015) were assessed. Univariate analyses of clinicopathologic and treatment factors were performed, and multivariable models were constructed to determine associations of operative approach (RPD or OPD) with perioperative outcomes. Results: Of the 1028 patients, 211 (20.5%) underwent RPD (4.7% conversions) and 817 (79.5%) underwent OPD. As compared with OPD, RPD patients had higher body mass index, rates of prior abdominal surgery, and softer pancreatic remnants, whereas OPD patients had a higher percentage of pancreatic ductal adenocarcinoma cases, and greater proportion of nondilated (<3 mm) pancreatic ducts. On multivariable analysis, as compared with OPD, RPD was associated with longer operative times [mean difference = 75.4 minutes, 95% confidence interval (CI) 17.5–133.3, P = 0.01], reduced blood loss (mean difference = −181 mL, 95% CI −355–(−7.7), P = 0.04) and reductions in major complications (odds ratio = 0.64, 95% CI 0.47–0.85, P = 0.003). No associations were demonstrated between operative approach and 90-day mortality, clinically relevant postoperative pancreatic fistula and wound infection, length of stay, or 90-day readmission. In the subset of 522 (51%) pancreatic ductal adenocarcinomas, operative approach was not a significant independent predictor of margin status or suboptimal lymphadenectomy (<12 lymph nodes harvested). Conclusions: Postlearning curve RPD can be performed with similar perioperative outcomes achieved with OPD. Further studies of cost, quality of life, and long-term oncologic outcomes are needed.